Physiologic profile of recreational male and female novice and experienced Tae Kwon Do practitioners - Toskovic, N. N.; Blessing, D.; Williford, H. N. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: Subjects, 28 recreational male and female novice and experienced Tae Kwon Do practitioners (age 19-42 years), were examined on 6 physiological parameters: body composition (BF%, skinfold measures), flexibility (sit-and-reach and leg-splits tests), lower and upper-body dynamic muscular strength (leg press and bench press), abdominal strength and endurance (1-minute timed, bent-knee sit-ups test), lower extremity explosive power (vertical jump-and-reach test), and cardiovascular endurance (graded exercise treadmill test). METHODS: Subjects were assigned to 1 of the 4 following groups: Tae Kwon Do experienced and trained men (MT), Tae Kwon Do experienced and trained women (FT), novice Tae Kwon Do men (MN), and novice Tae Kwon Do women (FN). RESULTS: Results of multiple testing procedures and comparison across groups indicated that Tae Kwon Do black belts were more athletically fit as compared with that of novice Tae Kwon Do practitioners of the same sex in spite of the fact that male and female black belts were older than their novice counterparts. Experienced Tae Kwon Do subjects were stronger as measured by lower body strength and showed better aerobic performance capacity as well as lower percent body fat. Additionally, MT subjects demonstrated higher flexibility. CONCLUSION: The highly diverse training, repeated and continuous use of the legs and arms alone or combined with maximal stretching, and high intensity exercise may account for observed differences among groups.